International migration, transfers of norms and home country fertility - Michel Beine; Frédéric Docquier; Maurice Schiff (Institute for the Study of Labor (IZA), 2008)
This paper examines the relationship between international migration and source country fertility. The impact of international migration on source country fertility may have a number of causes, including a transfer of destination countries' fertility norms and an incentive to acquire more education. We provide a rigorous test of the diffusion of fertility norms using original and detailed data on migration. Our results provide evidence of a strong transfer of fertility norms from migrants to their country of origin.
urn:nbn:de:101:1-2009011982
Keywords: J13; J61; O11; 330; International migration; endogenous fertility; human capital; social norms; Internationale Wanderung; Soziale Werte; Fruchtbarkeit; Bildungsverhalten; Migranten; Welt